Highly emissive CdTe nanowires grown in a phosphate buffer solution: FLIM imaging and spectroscopic studies - GOUNKO, IOURI; RAKOVICH, YURY; DONEGAN, JOHN (My University, 2007)
We present details on the formation and optical peroperties of CdTe nanowires, which were found to grow in a standard phosphate-buffered solution, including micro-photoluminescence and fluorescence lifetime imaging.
Proceedings of SPIE
ICONO 2007: Novel Photonics Materials; Optics and Optical Diagnostics of Nanostructures
PUBLISHED
Keywords: CdTe; quantum wires; self-assembly; FLIM imaging